Fabrication of Multilayers Electrodes and Electrolyte Via Screen Printing for Metal Supported Solid Oxide Fuel Cell - Abd.Rahman, Hamimah; Muhammad Amirul Adli Mashuri, (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Metal-Supported Solid Oxide Fuel Cell (MS-SOFC) were produced using a manual screen-printing method on 430 stainless steel (SS430) substrates. Each of MS-SOFC sample was fabricated by using manual screen printing with two different mesh screens which are 305 and 355. The fabrication of NiO-GDC composite anode powder was done by mixing 60wt% NiO and 40wt% GDC. Meanwhile, 50wt% LSCF and 50wt% GDC was mixed to produce LSCF-GDC composite cathode powder. NiO-GDC, LSCF-GDC and GDC powders went through calcination in the furnace at 950℃ for 2 hours. MS-SOFC samples with a different number of repetitions during the screen-printing process were sintered at 900℃ for 90 minutes. In this study, the phase analysis was conducted via X-Ray Diffraction (XRD) method for commercial powder and composite powders. A good XRD pattern was obtained without the presence of any secondary peak in composite anode and cathode powder. The XRD data obtained were analysed to obtain the lattice structure and crystallise size for all the commercial and composite powder. 24.59 nm, 24.38 nm, 13.34 nm are the average crystallise size for NiO, GDC and LSCF, respectively. Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS) were used to identify the thickness and distribution of elements on each MS-SOFC layer. As a result, the SOFC component layers fabricated by screen printed using 305-mesh screen at 10 times number of printings was selected as the ideal MS-SOFC sample. This is because the thickness of the layers obtained is lower compared to layers from mesh screens 305 and 355 at 15 and 20 times the number of printings which is 11.8 μm, 11.9 μm and 18.2 μm for anode, electrolyte and cathode, respectively. Thin electrode layer will produce low polarization resistance and can improve the SOFC performance itself.